Intraindividual validation of ventricular volume measurement by aortic and pulmonary arterial flow measurements in routine clinical cardiovascular magnetic resonance of congenital heart disease. (December 2016) - Kharabish, Ahmed; Ghandour, Fransis; Mkrtchyan, Naira; Meierhofer, Christian; Martinoff, Stefan; Ewert, Peter; Stern, Heiko; Fratz, Sohrab
Abstract: Introduction: To validate right and left ventricular stroke volume (RVSV & LVSV) measurements by forward flow stroke volume from aortic (AoSV) and pulmonary arterial (MPASV) measurements during routine cardiovascular magnetic resonance (CMR) in congenital heart disease (CHD). Methods: Retrospectively studied CMR of 147 consecutive patients (median age 22 years, range 0.5–64 years) with CHD. Patients with ventricular septal defects, mitral valve regurgitation or severe tricuspid-valve-regurgitation were excluded. 126 LVSV were compared to the AoSV. 99 RVSV were compared to the MPASV. Ventricular SV was determined using a routine standard stack of cine axial slices. Arterial forward flow SV was determined using a routine standard phase-velocity quantitative flow sequence. Results: AoSV correlated with LVSV by (r 2 = 0.9, p < 0.0001) and showed upper and lower limits of agreement in Bland Altman analysis of 11 ml and -12 ml, mean difference -1 ml. Similarly RVSV correlated with the accompanying MPASV (r 2 = 0.8, p < 0.0001) and showed upper and lower limits of agreement in Bland Altman analysis of 18 ml and -26 ml, and mean difference -4 ml. Conclusion: Measured ventricular SV correlates closely with SV, assessed by CMR flow measurement in the originating great artery in CMR of CHD. Highlights: Validate the CMR volumes measurements in CHD in routine clinical work. CMR ventricular SV correlates with SV flow in the great arteries in clinical CHD. CMR can be used confidently in distorted ventricular geometry in CHD.